(untitled) (Research, Society and Development, 2022)
The proper disposal and treatment of urban solid waste is one of the foundations for environmental preservation, especially in the Amazon region. Therefore, this study evaluated, through a documentary analysis, the management of solid waste in the 35 municipalities of Mato Grosso belonging to the Xingu river sub-basin. The Municipal Basic Sanitation Policy (Planos Municipais de Saneamento Básico - PMSB) developed by the mentioned municipalities were analyzed, evaluating documents and services aimed at solid waste management. It was observed that 68.6% of the municipalities are classified as small and the results indicate that 27.0% of the PMSB present flaws in their elaboration, and that 76.5% of the municipalities still use dumps for the disposal of their solid waste. It became evident that all municipalities have deficiencies in the development of programs aimed at recycling and reverse logistics. The difficulties and deficiencies faced by these municipalities are due, in most of the time, to the non-compliance with waste management policies by managers and the difficulties in tax collection, since the region is still far from the conditions to meet the requirements of the National Solid Waste Policy (Política Nacional de Resíduos Sólidos - PNRS). Thus, these municipalities should devote themselves to the development of consortium actions that would address the deficiencies and allow them to fulfill, more quickly, their obligations in relation to the PNRS.